Effectiveness of music therapy within community hospitals: an EMMPIRE retrospective study - Samuel N. Rodgers-Melnick; Rachael L. Rivard; Seneca Block; Jeffery A. Dusek (PAIN Reports, 2023)
Abstract. Introduction:. Given the challenges health systems face in providing effective nonpharmacologic treatment for pain and psychological distress, clinical effectiveness studies of evidence-based strategies such as music therapy (MT) are needed. Objectives:. This study examined changes in patient-reported outcomes (PROs) after MT and explored variables associated with pain reduction of ≥2 units on a 0 to 10 numeric rating scale (NRS). Methods:. A retrospective review was conducted on initial MT interventions provided to adults receiving community hospital care between January 2017 and July 2020. Sessions were included if participants reported pre-session pain, anxiety, and/or stress scores of ≥4 on the NRS. Data analysis included a bootstrap analysis of single-session changes in PROs and a logistic regression exploring variables associated with pain reduction (ie, ≥2 units vs <2 units). Results:. Patients (n = 1056; mean age: 63.83 years; 76.1% female; 57.1% White; 41.1% Black/African American) reported clinically significant mean reductions in pain (2.04 units), anxiety (2.80 units), and stress (3.48 units). After adjusting for demographic, clinical, and operational characteristics in the model (c-statistic = 0.668), patients receiving an MT session in which pain management was a goal were 4.32 times more likely (95% confidence interval 2.26, 8.66) to report pain reduction of ≥2 units than patients receiving an MT session in which pain management was not a session goal. Conclusion:. This retrospective study supports the clinical effectiveness of MT for symptom management in community hospitals. However, additional research is needed to determine which characteristics of MT interventions and patients influence pain change.